2020
DOI: 10.3390/nu12082424
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Dietary Selenium Intake and Genetics in Determining Cancer Risk and Outcome

Abstract: There is considerable interest in the trace element selenium as a possible cancer chemopreventive dietary component, but supplementation trials have not indicated a clear benefit. Selenium is a critical component of selenium-containing proteins, or selenoproteins. Members of this protein family contain selenium in the form of selenocysteine. Selenocysteine is encoded by an in-frame UGA codon recognized as a selenocysteine codon by a regulatory element, the selenocysteine insertion sequence (SECIS), in the 3′-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
(125 reference statements)
0
11
0
Order By: Relevance
“…Notably, evolutionary selection of certain genotypes may have enabled a better adaptation to nutritional restrictions, and render subjects less sensitive to poor supply in a Se-deficient environment [34]. A full overview of the potential interactions between variations in Se-related genes and health issues can be found elsewhere [35][36][37]. Notably, certain genotypes associate with autoimmune disease (AID) risk and autoantibody titers, e.g., in selenoprotein S (SELENOS) [38] or selenoprotein P (SELENOP) [39].…”
Section: Model Systems Inherited Diseases and Hierarchical Selenium Supplymentioning
confidence: 99%
“…Notably, evolutionary selection of certain genotypes may have enabled a better adaptation to nutritional restrictions, and render subjects less sensitive to poor supply in a Se-deficient environment [34]. A full overview of the potential interactions between variations in Se-related genes and health issues can be found elsewhere [35][36][37]. Notably, certain genotypes associate with autoimmune disease (AID) risk and autoantibody titers, e.g., in selenoprotein S (SELENOS) [38] or selenoprotein P (SELENOP) [39].…”
Section: Model Systems Inherited Diseases and Hierarchical Selenium Supplymentioning
confidence: 99%
“…Polymorphisms in selenoproteins are associated with variations in protein levels and pose a cancer risk to the system. These types of polymorphisms are seen in the 3'UTR of mRNA (Kadkol and Diamond, 2020). Studies have also reported an inverse relationship between cancer risk and Sepp1 levels (Cui et al, 2017).…”
Section: Selenoprotein Pmentioning
confidence: 99%
“…Selenium (Se) is an essential micronutrient; trace amounts are necessary for the function of the human body and it is mainly obtained through diet and/or nutritional supplements [ 4 ]. Se is a component of the selenoproteins (mostly in the form of amino acid selenocysteine) that participate in a wide range of cellular physiological processes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%